Climate factors and their relation regarding cone yield of stone pine (Pinus pinea L.) in the Kozak Basin, Turkey - Parlak S.; Kilci M.; Sayman M.; Akkaş M.E.; Bucak C.; Boza Z. (Mediterranean stone pine for agroforestry, 2013)
This study aims to reveal the factors that affect cone yield of both natural and planted stone pine (Pinus pinea L.) in Kozak Basin, Bergama, Izmir (Turkey). In the basin, productive and non-productive areas have been determined, according to long term observations. Topographical features of the basin, pollination properties and long term precipitation data have been analyzed. In addition, three meteorological stations have been established in places which can represent productive and non-productive areas of the basin. Productive areas have lower relative humidity and higher wind speed than non-productive areas. In nonproductive areas the number of days in which the temperature falls below -10ºC and relative humidity rates surpass 70% is higher than in productive areas. It has been determined that during pollination period a wind speed higher than 3 m/s is very effective in pollination. Likewise it is understood that pollination also is influenced negatively from precipitation occurring during pollination period, high relative humidity of air and extremely high or low temperatures. In non-productive areas it is determined that there is a temperature difference, reaching to 22ºC, between day and night. All these clues show that non-productive areas have a very similar characteristics of a typical “frost hollow (frost pocket)”.
AGROPINE 2011 International Meeting on Mediterranean Stone Pine for Agroforestery, 2011/11/17-19, Valladolid (Spain)